2021
DOI: 10.1080/10901027.2021.1918294
|View full text |Cite
|
Sign up to set email alerts
|

Identifying primary and secondary stressors, buffers, and supports that impact ECE teacher wellbeing: implications for teacher education

Abstract: Stress has been shown to negatively impact early childhood teachers' abilities to provide high quality, responsive environments for young children. Previous studies of early childhood teacher stress have focused on the tasks and responsibilities inherent in the job as well as on structural conditions within the field of early childhood education. The present study explored inter-and intra-personal dimensions of early childhood teacher stress and applied the Stress Process model to teachers' experience of work-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The TSS was created to assess the extent to which early childhood teachers “felt stressed” regarding a specified aspect of their teaching situation. The development of the items for the TSS was informed by theories (e.g., Lazarus and Folkman, 1984 ; Kyriacou, 2001 ) and the extant literature on early childhood teacher stress and stress coping (e.g., Whitaker et al, 2015 ; Roberts et al, 2016 ; Clayback and Williford, 2021 ; Tebben et al, 2021 ; Chen, 2022 ; Chen, under review ). For instance, the theoretical and empirical body of literature suggests that the lack of social support and high levels of teaching demands are two key sources of teacher stress.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The TSS was created to assess the extent to which early childhood teachers “felt stressed” regarding a specified aspect of their teaching situation. The development of the items for the TSS was informed by theories (e.g., Lazarus and Folkman, 1984 ; Kyriacou, 2001 ) and the extant literature on early childhood teacher stress and stress coping (e.g., Whitaker et al, 2015 ; Roberts et al, 2016 ; Clayback and Williford, 2021 ; Tebben et al, 2021 ; Chen, 2022 ; Chen, under review ). For instance, the theoretical and empirical body of literature suggests that the lack of social support and high levels of teaching demands are two key sources of teacher stress.…”
Section: Methodsmentioning
confidence: 99%
“…Data from the 2013 Gallup-Healthways Well-Being Index revealed that nearly half of the K-12 teachers (46%) reported experiencing high levels of daily stress during the school year, paralleling other exceedingly demanding professions, such as nurses (46%) and doctors (45%) ( Gallup, 2014 ). While teacher stress in the United States is pervasive in general, stress experienced by early childhood educators is particularly prevalent (e.g., Whitaker et al, 2015 ; Roberts et al, 2016 ; Tebben et al, 2021 ). For example, in their large-scale survey-based study of 2,199 preschool educators working with young children in 66 Head Start programs in Pennsylvania, Whitaker et al (2013) found that these educators experienced significantly poorer levels of mental health, with 23% of them reporting diagnosed depression compared to 17.6% of two national samples of peers with similar sociodemographic characteristics.…”
Section: The Prevalence Of Teacher Stress Among Early Childhood Teach...mentioning
confidence: 99%
See 2 more Smart Citations
“…Self-determination and COR have identified possible mechanisms by which this may occur: (1) promoting teachers' work engagement and quality by meeting their psychological needs, and (2) by reducing stress and facilitating teachers' use of energy for the acquisition of greater resources. Moreover, qualitative (e.g., Nitecki 2015;Tebben et al 2021;Zulauf and Zinsser 2019) and quantitative (e.g., Goddard et al 2015;Jung and Sheldon 2020;Lubienski et al 2008) studies suggest an interplay between program climate and culture and teachers' attitudes about parents. The present study extends such work by examining associations between programlevel supports, as reported by ECE program directors, and perceived support from families, as reported by teachers.…”
Section: The Present Studymentioning
confidence: 99%